Comparative assessment of grassland degradation dynamics in response to climate variation and human activities in China, Mongolia, Pakistan and Uzbekistan from 2000 to 2013. (December 2016) - Yang, Yue; Wang, Zhaoqi; Li, Jianlong; Gang, Chencheng; Zhang, Yanzhen; Zhang, Ying; Odeh, Inakwu; Qi, Jiaguo
Abstract: Quantifying the driving force is significant to understand the impact of climate variation and human activities on grassland degradation. In this study, we selected net primary productivity (NPP) as an indicator to quantitatively assess the relative roles of climate variation and human activities in China, Mongolia, Pakistan and Uzbekistan from 2000 to 2013. The results showed that 1.9% of grassland areas experienced degradation in Uzbekistan. By contrast, 29.6%, 16%, and 32.5% of grassland areas underwent restoration in China, Mongolia and Pakistan, respectively. Furthermore, 83.9%, 85.1%, 6.7% of restored grassland areas were influenced by climate variation and 65%, 79.1%, 11.6% of degraded areas were affected by human activities in Mongolia, Pakistan and Uzbekistan, respectively. The NPP variation also could be calculated to evaluate the impacts of these factors and results were consistent with the findings based on area. Therefore, climate variation dominated grassland restoration, human activities dominated degradation in Mongolia and Pakistan, and Uzbekistan was just the opposite. In China, 38.5% of the grassland restoration areas was caused by climate variations compared with 38% induced by human activities. On the contrary, 37.4% of grassland degradation was caused by climate variation and 30% resulted from human activities. In addition, the results based on NPP variation revealed that 39.2% of restored grassland areas were influenced by human activities and 38.2% of degraded areas were affected by climate variation. Therefore, climate variation dominated grassland degradation and the driving force of restoration was determined by the effectiveness of environmental protection programs. Highlights: NPP was used to assess the relative role of driving factor in grassland degradation. Climate variation benefits the restoration, human activities promote degradation. Contributions of the two factors varied greatly in these four countries. Environmental protect programs are beneficial to the grassland restoration.